2009
DOI: 10.1590/s0034-89102009000200007
|View full text |Cite
|
Sign up to set email alerts
|

Fatores preditivos de incapacidades em pacientes com hanseníase

Abstract: OBJECTIVE:To analyze predictive factors in the progression of the disability grade in patients with leprosy.METHODS: A retrospective cohort study followed up 595 patients with disability registered at a healthcare unit in the city of Belo Horizonte (Southeastern Brazil) from 1993 to 2003. Patients' sociodemographic and clinical information was collected from the respective medical records. Comparisons were made between the disability grade upon admission and at the end of treatment using a marginal homogeneity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
40

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 12 publications
2
32
1
40
Order By: Relevance
“…Physical disability affects approximately 23.0% of leprosy patients after discharge 9 . The evaluation and monitoring of the state of the patients are essential to the preservation of the structure and function of the peripheral nerve, contributing to the early identification of neural complications and disabilities 6 .…”
Section: Palavrasmentioning
confidence: 99%
“…Physical disability affects approximately 23.0% of leprosy patients after discharge 9 . The evaluation and monitoring of the state of the patients are essential to the preservation of the structure and function of the peripheral nerve, contributing to the early identification of neural complications and disabilities 6 .…”
Section: Palavrasmentioning
confidence: 99%
“…15 Patients and professionals equate fi nishing the treatment with a discharge from the Prevention and Rehabilitation of Disability due to Leprosy service (PRD), which is mistaken. 8 Croft et al 3 showed that in multibacillary cases, which treatment begins with nerve function already altered, there is a risk of up to 65% of presenting new damage during treatment; in paucibacillary leprosy, the risk is 16%.…”
mentioning
confidence: 99%
“…No Brasil, aproximadamente 23% dos pacientes hansenianos apresentam algum tipo de incapacidade após a alta 5,6 . Mesmo assim, o Ministério da Saúde preconiza que, após a conclusão do tratamento adequado, ou seja poliquimioterapia por seis a doze meses, o paciente pode ser considerado como curado e retirado das estatísticas oficiais.…”
unclassified